2009
DOI: 10.1002/pits.20389
|View full text |Cite
|
Sign up to set email alerts
|

The influence of gender on the likelihood of using soft social power strategies in school consultation

Abstract: The social power typology developed originally by French and Raven in 1959 and revised by Raven in 1965 and 1992 was applied to study school consultation. Specifically, we investigated how the gender of school psychologist consultants and teacher consultees influence how likely consultants are to use soft power strategies, identified as those drawing on expert, referent, informational, legitimate dependency, and legitimate position power. A modified version of the Interpersonal Power Inventory was mailed to 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…Such factor structure is similar to the one obtained by Erchul et al (4-factor structure [12], and in contrast to others, e.g., 7 factors distinguished by Raven et al [3] or 2 distinguished in [4,13,16,17]). Although 2-factor solution emerges more frequently, the factorial structure of the original 11 power bases is still to be established.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Such factor structure is similar to the one obtained by Erchul et al (4-factor structure [12], and in contrast to others, e.g., 7 factors distinguished by Raven et al [3] or 2 distinguished in [4,13,16,17]). Although 2-factor solution emerges more frequently, the factorial structure of the original 11 power bases is still to be established.…”
Section: Discussionsupporting
confidence: 89%
“…We supported the view that power bases were not independent and they constituted factors [3,[12][13][14][15][16][17]. We also confirmed that people complied with their superiors' will for different reasons that accounted for styles of compliance.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Some, but not all, of these include: (a) consultant leadership style (Kelleher, Riley-Tillman, & Power, 2008;Tysinger, Tysinger, & Diamanduros, 2009), (b) consultee and consultant skill level (Gettinger, Stoiber, & Koscik, 2008;Lewis & Newcomer, 2002;Sterling-Turner, Watson, & Moore, 2002;Wilkinson, 2003), (c) social power strategies (Getty & Erchul, 2009;Wilson, Erchul, & Raven, 2008), (d) acceptability of treatment plans (Chitiyo & Wheeler, 2009;Kelleher, et al, 2008;Noell et al, 2005;Sanetti & Kratochwill, 2008;Segool, et al, 2007;Tysinger, et al, 2009;Wilkinson, 2003), (e) time of consultant and teacher to implement the intervention (Gansle & Noell, 2008;Gonzalez, Nelson, Gutkin, & Shwery, 2004;Lane, et al, 2004;Sanetti & Kratochwill, 2008), and (f) training provided to consultee (Sanetti & Kratochwill, 2008;Sterling-Turner et al, 2002). When treatment integrity is not assessed during the consultation process, behavior change cannot be fully attributed to the effectiveness of the treatment plan (Lane et al, 2004).…”
Section: Plan Implementationmentioning
confidence: 99%